Islamic Value Education and Reconstruction of Civilization in Disruptive Era - Taofik Andi Rachman; Euis Latipah; Aan Hasanah; Bambang Samsul Arifin (Islamic Research, 2022)
Today, the world is experiencing the development of science and technology on all fronts. The most notable developments are in the field of information and communication technology. So that information from all over the world can be obtained quickly. However, on the other hand, the problems faced by humans are increasingly complex. Value decline in character education and value application in Islamic civilization occurred. The need to revive Islamic values in the era of industrial revolution 4.0 is the answer so that human do not forget their identity. This study's purpose is to describe a reconstruction of Islamic civilization in an era of value decline based on research, expert opinion, and historical experience. This research uses the library research method. The results of this study see that the reconstruction of civilization is an effective way of changing mental habits that have long hindered awakening. The immaterial factor is the primary condition of the establishment of civilization. Part of the factors is the worldview and thought of value. Transforming worldview and value with da'wah and education must adjust to technology development today. Social networking sites, video-sharing sites, chat apps, video conference apps, and other digital platforms are part of the reconstruction of civilization.